2012
DOI: 10.1177/000348941212100503
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Carcinoma in Situ of Wharton's Duct after Chronic Obstructive Sialadenitis: Inflammation as the Cause of Malignancy?

Abstract: A case of bilateral carcinoma in situ of Wharton's duct after chronic sialadenitis is reported. The patient, a 54-year-old man, complained of recurrent pain and swelling in the left lower submandibular region. Computed tomography showed large stones in the hilar area of both submandibular glands. The patient underwent bilateral submandibular excision. Histologic and immunohistochemical examination revealed squamous metaplasia with areas of carcinoma in situ in both right and left ducts adjacent to the calculus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Salivary duct involvement was observed in two primary SCCs, supporting the possible ductal origin of primary SCC of the salivary gland. Consistently, SCCs in situ arising from salivary ductal epithelium have been reported [ 6 , 13 ]. Flynn et al [ 3 ] reported presence of squamous metaplasia within the ductal epithelium adjacent to invasive carcinoma in a fraction of primary SCC cases.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Salivary duct involvement was observed in two primary SCCs, supporting the possible ductal origin of primary SCC of the salivary gland. Consistently, SCCs in situ arising from salivary ductal epithelium have been reported [ 6 , 13 ]. Flynn et al [ 3 ] reported presence of squamous metaplasia within the ductal epithelium adjacent to invasive carcinoma in a fraction of primary SCC cases.…”
Section: Discussionsupporting
confidence: 71%
“…The histologic features were compared between the primary tumor and metastatic SCC. Regarding the previous studies, the possible presence of squamous ductal metaplasia, ductal dysplasia, or a ductal carcinoma component was investigated to help elucidate the pathogenesis of primary SCC of the salivary gland [ 6 , 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Gallego et al reported a case with small calculi in the submandibular gland and obstructive sialadenitis, of whom histopathological examination revealed carcinoma in situ of Wharton's duct, and suggested that chronic inflammation might have been a probable factor for the development of malignancy. 10 In conclusion, the case presented herein is important, as the patient developed recurrent sialolithiasis despite submandibular gland excision and had also deep neck infection. As the Wharton's duct can promote the sublingual gland drainage, it is important for the prevention of sialadenitis of the sublingual gland to preserve a part of the Wharton's duct after the excision of the mandibular gland for sialolithiasis.…”
Section: Discussionmentioning
confidence: 74%
“…Batzakakis et al and Hasegawa et al reported cases of salivary coexisting AdCCs and sialolithiasis in the submandibular region, 3,4 but the descriptions were unclear on the timing of each disorder. 3,4,10 Owing to medical advances, if the size of AdCC is ϕ 5 mm or more, the diagnosis of the coexisting disorders may be possible by CT, US, or other imaging technique before surgery, but if the coexisting AdCC is small (ϕ 5 mm or less), it may be very difficult to diagnose it before examining the surgical specimen. In the case of our patient and in the other cases in the literature (the 2 mentioned cases and a case of parotid, neoplastic lesions coexisting with sialolithiasis), the malignancies were not suspected before surgery.…”
Section: Discussionmentioning
confidence: 99%